Examining the Pedagogical and Institutional Phenomena that Influence the Facilitation of Critical Consciousness - Pollard, Barb Anne (Alberta Journal of Educational Research, 2020)
This study engaged grounded theory methodology to explore how critical pedagogy shaped and influenced the development of critical consciousness among preservice teacher candidates. The teacher participants revealed that facilitating critical consciousness was a complex process influenced by pedagogical and institutional mechanisms. The pedagogical mechanism of coercive power and the institutional mechanism of compressed time both limited opportunities for student agency and constrained the development of critical consciousness. Two professors were successful in countering the negative consequences of these institutional and pedagogical mechanisms by enacting a legitimate form of power and facilitating dialogical learning contexts. These efforts are highlighted in the paper as key attributes of consciousness raising learning experiences among the preservice teachers. Keywords: preservice teachers, critical pedagogy, critical consciousness, Faculty of Education, course-based learning experiences Cette étude, qui repose sur une méthodologie inspirée de la théorie à base empirique, explore la mesure dans laquelle la pédagogie critique a influencé le développement d’une conscience critique chez des enseignants en formation. Les enseignants participants ont révélé que la promotion de la conscience critique est un processus complexe qui est influencé par des mécanismes pédagogiques et institutionnels. Le mécanisme pédagogique du pouvoir coercitif et le mécanisme institutionnel du calendrier comprimé limitent tous les deux la marge de manœuvre des étudiants et contraignent le développement de la conscience critique. Deux professeurs ont réussi à contrer les conséquences négatives de ces mécanismes institutionnels et pédagogiques en exerçant une forme de pouvoir légitime et en facilitant des contextes d’apprentissage dialogique. L’article présente ces efforts comme étant les caractéristiques principales des expériences d’apprentissage ayant favorisé la prise de conscience chez les enseignants en formation. Mots clés: enseignants en formation; pédagogie critique; conscience critique; faculté d’éducation; expériences d’apprentissage basées sur les cours